Functional Interaction between the Herpes Simplex Virus Type 1 Polymerase Processivity Factor and Origin-Binding Proteins: Enhancement of UL9 Helicase Activity - Trego, Kelly S. (American Society for Microbiology, 2003)
The origin (ori)-binding protein of herpes simplex virus type 1 (HSV-1), encoded by the UL9 open reading frame, has been shown to physically interact with a number of cellular and viral proteins, including three HSV-1 proteins (ICP8, UL42, and UL8) essential for ori-dependent DNA replication. In this report, it is demonstrated for the first time that the DNA polymerase processivity factor, UL42 protein, provides accessory function to the UL9 protein by enhancing the 3′-to-5′ helicase activity of UL9 on partially duplex nonspecific DNA substrates. UL42 fails to enhance the unwinding activity of a noncognate helicase, suggesting that enhancement of unwinding requires the physical interaction between UL42 and UL9. UL42 increases the steady-state rate for unwinding a 23/38-mer by UL9, but only at limiting UL9 concentrations, consistent with a role in increasing the affinity of UL9 for DNA. Optimum enhancement of unwinding was observed at UL42/UL9 molecular ratios of 4:1, although enhancement was reduced when high UL42/DNA ratios were present. Under the assay conditions employed, UL42 did not alter the rate constant for dissociation of UL9 from the DNA substrate. UL42 also did not significantly reduce the lag period which was observed following the addition of UL9 to DNA, regardless of whether UL42 was added to DNA prior to or at the same time as UL9. Moreover, addition of UL42 to ongoing unwinding reactions increased the steady-state rate for unwinding, but only after a 10- to 15-min lag period. Thus, the increased affinity of UL9 for DNA most likely is the result of an increase in the rate constant for binding of UL9 to DNA, and it explains why helicase enhancement is observed only at subsaturating concentrations of UL9 with respect to DNA. In contrast, ICP8 enhances unwinding at both saturating and subsaturating UL9 concentrations and reduces or eliminates the lag period. The different means by which ICP8 and UL42 enhance the ability of UL9 to unwind DNA suggest that these two members of the presumed functional replisome may act synergistically on UL9 to effect initiation of HSV-1 DNA replication in vivo.